2008
DOI: 10.1590/s1516-14392008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer radar absorbing material processing by using polymeric nonwoven and conducting polymer

Abstract: This study shows the processing of radar absorbing multilayer structures based on nonwoven substrates of polyacrylonitrile and poly (ethylene terephthalate) impregnated with a polyaniline and polyurethane mixture. Processed materials with different parameters -layer stacking and impregnated faces -were evaluated considering the incident radiation attenuation in the frequency range of 8 to 12 GHz. The results show the influence of the quantity, types and thickness of the impregnated layers. Scanning electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
0
20
0
2
Order By: Relevance
“…SEM analyses (Figures 1 and 2) show the presence of NTC agglomerates after the dispersion in the resin. According to literature 63,64 these agglomerates act as electric conduction islands and favor the interaction of the electromagnetic wave with the material. It is also observed that the RAM samples evaluated behave as a narrow band absorber (resonance peak in the range of 9.5 and 11 GHz) in the evaluated frequency range (8.2 to 12.4 GHz).…”
Section: Electromagnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM analyses (Figures 1 and 2) show the presence of NTC agglomerates after the dispersion in the resin. According to literature 63,64 these agglomerates act as electric conduction islands and favor the interaction of the electromagnetic wave with the material. It is also observed that the RAM samples evaluated behave as a narrow band absorber (resonance peak in the range of 9.5 and 11 GHz) in the evaluated frequency range (8.2 to 12.4 GHz).…”
Section: Electromagnetic Propertiesmentioning
confidence: 99%
“…For definition 63,64 , the real relative permittivity values (ε = ε' -jε") are always higher than the unit. A material which presents value zero of dielectric loss it will have the values of the permittivity complex parameters ε'=1 e ε"=0.…”
Section: Electromagnetic Propertiesmentioning
confidence: 99%
“…Dentre os aditivos mais comumente utilizados no processamento desses materiais destacam-se as ferritas, a ferro carbonila, o negro de fumo e os polímeros condutores [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Considerando-se os polímeros condutores, vale ressaltar a sua crescente importância na área de MARE, em função de suas interessantes propriedades físicas (eletrônicas), estabilidade química, facilidade de síntese, relativa facilidade de processamento e, principalmente, menor massa específica em relação às ferritas e à ferro carbonila [2,[9][10][11][12][13][14][15][16][17][18] . Os polímeros condutores têm despertado crescentes interesses científicos e tecnológicos nos últimos anos, devido às suas propriedades, em particular, sua condutividade elétrica.…”
Section: Introductionunclassified
“…Using the experimental data collected on the single-layer materials, it is possible to simulate the behavior of two-layer RAM's using Equation 5. Figure 7 shows the results of simulations when these materials are combined in different configurations to produce a material with a total thickness of 10 mm.…”
Section: Resultsmentioning
confidence: 99%
“…that will act as a support for an energy absorbing center. The absorbing center may consist of, for example, a conducting polymer with good mechanical and chemical properties and whose electrical conductivity can be modulated 5 . The behavior of conducting polymers illuminated by electromagnetic radiation in the X-band (8 -12 GHz) has been studied to understand how the conductivity of these polymers affect the absorption of electromagnetic energy and how these materials can be used in the production of RAM's [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%